Brilliant Corners: Approaches to Jazz and Comics. Issue 1 (30th August 2016) - Pillai, Nicolas; Priego, Ernesto
Abstract : The call for papers Brilliant Corners: Approaches to Jazz and Comics was published on 30 July 2015. In it, the editors made a public invitation for scholarship that proposed meeting points between the disciplines of jazz studies and comics studies. This editorial discusses the motivations for the collection, the editorial methodology, and the research articles included. Finally, the editors suggest some areas in which jazz studies and comics scholarship might address under-researched and fertile topics.